CCN6 (WISP3): a new anti-cancer therapy? - Leask, Andrew (Springer Netherlands, 2010)
The CCN family of matricellular proteins are dysregulated in cancers, and may strategies targeting them may represent novel approaches to treating these diseases. A recent study from Huang and colleagues (Cancer Res. 70: 3340-50, 2010) suggests that CCN6 (WISP3) is downregulated in aggressive breast cancers, and this phenomenon may result in the promotion of tumor survival. CCN6 may represent a novel therapeutic approach to breast cancer.